Defect tolerance in CsPbI3: reconstruction of the potential energy landscape and band degeneracy in spin–orbit coupling. Issue 6 (7th January 2022) - Ming, Chen; Wang, Han; West, Damien; Zhang, Shengbai; Sun, Yi-Yang
Abstract : Different degeneracy between the conduction band and defect state leads to reconstruction of the potential energy surface with spin-orbit coupling and gives rise to defect tolerance in CsPbI3 . Abstract : Lead halide perovskites have been intensively developed to be high-performance photovoltaic and optoelectronic materials, where the unique defect tolerance properties are believed to contribute to their excellence. However, defect tolerance, especially for the donors, has not been conclusively understood yet. Using hybrid functional calculations including spin–orbit coupling (SOC), we study the intrinsic defects of γ-CsPbI3 . With a sufficiently large supercell and full structural relaxation, we show that most of the donor levels are deep in hybrid functional calculations, but become shallow due to the strong SOC effect, which reconstructs the potential energy surfaces of the donors by eliminating the large structural distortions. By quantifying the variation of electronic and elastic energies associated with defects, we show how the SOC effect changes the energy balance and reconstructs the defect structures. We reveal the decisive role of degeneracy of electronic states in the SOC effect, which significantly downshifts the conduction band minimum due to the quasi-three-fold degeneracy of Pb 6p orbitals, but has little effect on the non-degenerate defect states.